Professores em formação no contexto de fronteira Brasil/ Guyana: representações sobre a língua inglesa - Lima, Fernanda Sousa (2015)
This study aims to examine how representations about the varieties of Englishin Bonfim influence on the identity construction of the English teacher in formation process. The Participants of this survey were seven teachers in training at the State University of Roraima at the nucleus of Bonfim municipality, in the bordering Brazil/ Guyana. Its foundation is guided by authors of Applied Linguistics of the area that, for its hybrid nature approaches from other fields of social and human sciences. So, to answer the goal that this research suggests we rely on the concept of social representations in theoretical perspective of Jodelet (1989) main contributor to the French sociologist Serge Moscovici. This research is qualitative ethnographic, a case study. The generation records was undertaken through participant observation , the construction of the field diary , the sociolinguistic survey , focus group and semi-structured interviews The analysis pointed prestigious representations of the British or American varieties and Guyanese variety seen in the representation of disfavor. Such representations were shown in intrinsic relationship as the way that researched people in their explained future action or as they say exercise their practice.